STUDI EVALUATIF IMPLEMENTASI STANDAR PELAYANAN MINIMAL (SPM) PENDIDIKAN DASAR DI KABUPATEN BANTUL - Esti Setiawati (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This research aimed to evaluate the implementation of Basic Education Minimum Service Standards (MSS) in Bantul District. The result were the description of 27 achievement indicators of Basic Education Minimum Service Standards (MSS) and the report of result evaluation implementation. The research method used quantitative and qualitative research, with the evaluation research type. The evaluation model used Robert E. Stake's Countenance Evaluation Model which includes Antecedent (Context), Transaction (process), and Outcome (outcome) evaluation, while data analysis technique in this research is quantitative descriptive and qualitative analysis technique. The results showed that 27 of Achievement Indicators (AI) of Basic Education Minimum Service Standard (MSS) slightly increased on some indicators from the previous year. Description of the results of the study were: 1) for the level of elementary / MI level, AI 1-14 that has been fulfilled 100% that is AI 1, 12, and 13, while AI 15-27 has been fulfilled 100% that is AI 20 and 21; 2) for junior high school / MTs, AI 1-14 that has been fulfilled 100% that is AI 1, 12, and 13, while AI 15-27 that has been fulfilled 100% that have been reached was 100% such as 20 AI; 3) to reach the MSS achievement gap, the roadmap for fulfilling the Minimum Service Standard for Basic Education in 2017-2018.